A DARK ENERGY CAMERA SEARCH FOR AN OPTICAL COUNTERPART TO THE FIRST ADVANCED LIGO GRAVITATIONAL WAVE EVENT GW150914 - Soares-Santos, M.; Kessler, R.; Berger, E.; Annis, J.; Brout, D.; Buckley-Geer, E.; Chen, H.; Cowperthwaite, P. S.; Diehl, H. T.; Doctor, Z.; Drlica-Wagner, A.; Farr, B.; et al. (Iop Publishing Ltd, 2016)
We report the results of a deep search for an optical counterpart to the gravitational wave (GW) event GW150914, the first trigger from the Advanced LIGO GW detectors. We used the Dark Energy Camera (DECam) to image a 102 deg(2) area, corresponding to 38% of the initial trigger high-probability sky region and to 11% of the revised high-probability region. We observed in the i and z bands at 4-5, 7, and 24 days after the trigger. The median 5 sigma point-source limiting magnitudes of our search images are i = 22.5 and z = 21.8 mag. We processed the images through a difference-imaging pipeline using templates from pre-existing Dark Energy Survey data and publicly available DECam data. Due to missing template observations and other losses, our effective search area subtends 40 deg(2), corresponding to a 12% total probability in the initial map and 3% in the final map. In this area, we search for objects that decline significantly between days 4-5 and day 7, and are undetectable by day 24, finding none to typical magnitude limits of i = 21.5, 21.1, 20.1 for object colors (i - z) = 1, 0, - 1, respectively. Our search demonstrates the feasibility of a dedicated search program with DECam and bodes well for future research in this emerging field.
Keywords: binaries: close; catalogs; gravitational waves; stars: neutron; surveys